The role of citations and other metrics to assess research quality - Lindgreen, Adam; Di Benedetto, C. Anthony; Brodie, Roderick J.; Schäfers, Tobias (How to Achieve Societal Impact through Engaged and Collaborative Scholarship. A Guide to Purposeful Marketing Research)
Researchers are under constant pressure to demonstrate the quality of their research and to excel in various research quality assessments. What, however, constitutes high-quality research? Most universities use accepted lists of top-tier journals, citation counts, or other metrics to assess the value of research contributions. We explore the different metrics by which research contributions are evaluated. First, we outline how research quality has been assessed based on journal metrics, article-level metrics, and author-level metrics, all of which aim to quantify the quality of an author’s research output. These metrics provide at least some indication of the impact and value of an academic’s stream of research. Second, we consider the issue of value beyond the commonly accepted metrics of article counts and citations. Specifically, we describe how the Declaration of Research Assessment makes recommendations on how to improve assessments of research quality. We conclude by distilling these issues into several pieces of advice to new and mid-career academics regarding strategies and challenges in navigating research quality assessments.